Student Response to the Application of Augmented Reality Media with RME Approach - Ahmad Budi Sutrisno; Hamzah Upu; Dr. Rusli, MS, (International Journal of Scientific Research and Management (IJSRM), 2024)
The use of technology in learning is increasingly becoming a major concern in the world of education. One innovation that attracts attention is the application of Augmented Reality (AR) Media with a Realistic Mathematics Education (RME) approach in mathematics learning. This study aims to investigate the response of students to the application of AR media with the RME Approach in the context of mathematics learning. Qualitative quantitative research methods are used with experiments that accept learning with AR media and the RME Approach. Data collection instrument questionnaire student response to the media used. The results of the study are expected to provide a deeper understanding of how students respond to the application of AR media with the RME Approach. The implications of these findings can be used to improve the design of mathematics learning that is more interactive and relevant to the needs of learners in this technological era. In conclusion, the application of AR media with the RME approach has the potential to improve student response and the effectiveness of mathematics learning